2021
DOI: 10.1021/acsomega.1c03820
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation Dynamics of Nitric Oxide from N-Acetylcysteine- or N-Acetylpenicillamine-bound Roussin’s Red Ester

Abstract: The photochemical release of nitric oxide (NO) from a NO precursor is advantageous in terms of spatial, temporal, and dosage control of NO delivery to target sites. To realize full control of the quantitative NO administration from photoactivated NO precursors, it is necessary to have detailed dynamical information on the photodissociation of NO from NO precursors. We synthesized two new water-soluble Roussin’s red esters (RREs), [Fe2(μ-N-acetylcysteine)2(NO)4] and [Fe2(μ-N-acetylpenicillamine)2(NO)4], which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…70,71 Recent work by Lim et al focused on the cysteine-derived complexes FE1-FE3 which displayed excellent water solubility, suitable to complete an in-depth study into their photodissociation dynamics using femtosecond time-resolved infrared spectroscopy. 72 The thermal stability of the complexes FE2 and FE3 in water is around five times greater than the simple cysteine derivative FE1. Probing the excited state for FE1-FE3 revealed that they released one NO • to form [Fe 2 ((μ-RS) 2 (NO) 3 ], or relaxed to the ground state without photodeligation via an electronically excited intermediate state.…”
Section: Miscellaneous Examplesmentioning
confidence: 99%
“…70,71 Recent work by Lim et al focused on the cysteine-derived complexes FE1-FE3 which displayed excellent water solubility, suitable to complete an in-depth study into their photodissociation dynamics using femtosecond time-resolved infrared spectroscopy. 72 The thermal stability of the complexes FE2 and FE3 in water is around five times greater than the simple cysteine derivative FE1. Probing the excited state for FE1-FE3 revealed that they released one NO • to form [Fe 2 ((μ-RS) 2 (NO) 3 ], or relaxed to the ground state without photodeligation via an electronically excited intermediate state.…”
Section: Miscellaneous Examplesmentioning
confidence: 99%